Supply chain costing and performance management - Cokins, Gary; Pohlen, Terrance; Klammer, Thomas P., 1944- (Wiley, 2021)
"This book is a "how-to" guide to assist managers and employee teams to obtain interenterprise cost information on supply chain processes. It provides techniques for obtaining accurate cost and performance information on the activities performed within their firm and on activities performed by other trading partner firms comprising key processes within the supply chain. The techniques and approaches comprising the book were developed from supply chain costing practices implemented by leading-edge firms. Readers will understand how they can have access to reasonably accurate costs and profit margins involved with suppliers, products, stock keeping units (SKUs), service-lines, channels, and customers. In addition, they will have visibility and transparency to the activity costs in the various end-to-end business processes for each of those including the "drivers" for each type of cost. This information will provide managers with insights to make better decisions to improve an organizations performance and profitability."--